REGARDING THE CLASSIFICATION OF INTERNATIONAL TRANSPORT CORRIDORS PASSING THROUGH THE TERRITORY OF UZBEKISTAN - Rustamov Javansher Istamjon ogly (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article discusses the classification and description of transport corridors, shows that there are several criteria for classifying transport corridors and what these criteria consist of. The article also discusses transport corridors that meet the interests of Uzbekistan.